2013
DOI: 10.3892/etm.2013.1054
|View full text |Cite
|
Sign up to set email alerts
|

7,8-Dihydroxycoumarin inhibits A549 human lung adenocarcinoma cell proliferation by inducing apoptosis via suppression of Akt/NF-κB signaling

Abstract: The Akt/NF-κB pathways are involved in numerous anti-apoptotic and drug-resistance events that occur in non-small cell lung cancer (NSCLC). In the present study, the role of 7,8-dihydroxycoumarin in the regulation of the anti-apoptotic Akt and NF-κBp65 signaling pathways was explored. A549 human lung adenocarcinoma cells were exposed to 7,8-dihydroxycoumarin with a final concentration of 25, 50 and 100 μmol/l for 48 h. Quantitative polymerase chain reaction (PCR) and western blotting were performed to detect m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Several compounds have been found to exhibit attractive therapeutic potential for psoriasis though inhibiting NF-κB signaling pathway [10,[40][41][42][43]. Daphnetin was reported to inhibit proliferation and inflammation by regulating the NF-κB signaling pathway [13,16,17]. In order to investigate whether daphnetin-mediated inhibition of proliferation and inflammatory response in HaCaT keratinocytes is resulted from NF-κB signaling inactivation, p65 phosphorylation and p65 nuclear translocation were detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several compounds have been found to exhibit attractive therapeutic potential for psoriasis though inhibiting NF-κB signaling pathway [10,[40][41][42][43]. Daphnetin was reported to inhibit proliferation and inflammation by regulating the NF-κB signaling pathway [13,16,17]. In order to investigate whether daphnetin-mediated inhibition of proliferation and inflammatory response in HaCaT keratinocytes is resulted from NF-κB signaling inactivation, p65 phosphorylation and p65 nuclear translocation were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Daphnetin (7,, a natural coumarin compound isolated from Daphne odora var., exhibits broad bioactivities including anti-proliferation and anti-inflammation [11,12]. Daphnetin was found to inhibit A549 human lung adenocarcinoma cell proliferation by inducing apoptosis via suppression of Akt/NF-κB signaling [13]. Daphnetin ameliorates 7,12-dimethylbenz [a] anthracene-induced mammary carcinogenesis through dual inhibition on Nrf-2-Keap1 and NF-κB pathways [14].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, great effort is being made to identify potent natural antioxidants with neuroprotective potential, due to their low toxicity and absence of clear side effects. Daphnetin, a natural antioxidant, exhibits a variety of biological effects, including anti-inflammatory and antitumor effects (14). Recently, studies have demonstrated that daphnetin exhibits a neurotrophic effect on peripheral nerve regeneration by suppressing nuclear factor-κB expression (15), provides a neuroprotective effect against glutamate-induced toxicity in immortalized mouse hippocampal HT22 cells and ischemic brain injury (16), and prevents excitotoxicity by inhibiting the N-methyl D-aspartate receptor subtype 2B -containing receptors and the subsequent calcium overload in cultured cortical neurons (17).…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB/AKT signaling pathway is involved in the MDR reversal of CIK. It has been reported that activation of NF-κB followed by Akt phosphorylation has a role in the regulation of cell survival, apoptosis and drug resistance (8,9). The present study therefore investigated whether the intracellular AKT/NF-κB signaling pathway was involved in the effects of CIK on MDR.…”
Section: Cik Reduces Mdr-associated Gene Expression In U87mg/ddpmentioning
confidence: 93%